Problems of Speaking Skills in Arabic for Non-Native in Malaysia A Systematic Literature Review - Abu Bakar, Radhwa; Hannani, Nur Nabilah (Selangor International Islamic University College (KUIS), 2020)
Speaking skill in a second language or foreign language is part of transmission skills needed in practicing a language itself. Besides, it is an integrated process involving both tongue and conscious mind in using languages, which happen to be the biggest problem for students in using second language. Based on that reason, this research aimed to generally identify level of speaking skill in Arabic language among schools and universities students, and secondly to discover any related internal, external, and linguistic factors that cause the problem to happen. PRISMA (Preferred Reporting Items for Systematic reviews and Meta- Analysis) technique in systematic review methodology is used to analyse literature reviews. From 283 related articles found on Scopus and Google Scholar, 15 articles were selected and sorted. Based on this study, it showed that level of speaking skill in Arabic language among students decreased due to internal, external and linguistic factors which are lack of confidence, discouraging environment, lack of encouragement between students and teacher, and vocabulary deficiency. Thus, the researcher come up with several suggestions for future study as the solution to this issue.